1903 S.C. Acts 127-28, no. 86, § 1 - (:unkn) unknown (My University, 1903)
[I]t shall be unlawful for any one to carry about the person, whether concealed or not, any pistol less than twenty inches long and three pounds in weight; and it shall be unlawful for any person, firm or corporation to manufacture, sell or offer for sale, lease, rent, barter, exchange, or transport for sale or into this state, any pistols of less length and weight.
Keywords: CARRY; TRANSFER, MANUFACTURE & POSSESSION